Effect of Ionic Liquid Electrolyte on Electrochemical and Electrocatalytical Behaviours of Tri-Iron Cluster - LI*, ZHIMEI; ZENG, XIANGHUA; ZHONG, DINGYI; HE, FANG; NIU, ZHIGANG (Asian Journal of Chemistry, 2009)
The tri-iron cluster, [Fe3(μ3-S)2(CO)9], has been reported as a catalysis to proton reduction at low overpotential. In this paper, the electrochemical behaviour of the tri-iron cluster and its catalytic effect on hydrogen evolution were investigated further by using ionic liquid (1-dodecane-3-methylimidazolium tetrafluoroborate, IL) as electrolyte in dichloromethane, considering that IL has unique chemical and physical properties. In contrast to the conventional electrolytes (such as [NBu4]BF4), the IL electrolyte increases the stability of the monoanionic radical generated from the first reduction and the electrocatalytic efficiency on proton reduction has also been improved.